2018
DOI: 10.1111/rssc.12272
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Image-Based Statistical Shape Analysis of Brain Tumours

Abstract: Summary. We propose a curve-based Riemannian geometric approach for general shape-based statistical analyses of tumours obtained from radiologic images. A key component of the framework is a suitable metric that enables comparisons of tumour shapes, provides tools for computing descriptive statistics and implementing principal component analysis on the space of tumour shapes and allows for a rich class of continuous deformations of a tumour shape. The utility of the framework is illustrated through specific st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…We presented the first approach at assessing the effectiveness of 3D shape and surface radiomic features extracted from the tumor habitat (enhancing lesion, and T 2w /FLAIR hyperintense peri-lesional regions) to differentiate tumor progression from PsP on conventional MR scans (Gd-c T 1w , T 2w , FLAIR). Our work was based on the rationale that there are observable 3-dimenstional shape and surface irregularities encountered on the enhancing lesion as well as the perilesional boundaries in patients with tumor recurrence (potentially due to aggressive tumor infiltration and disruption) as compared to those with benign pseudoprogression, which will likely have more regular boundaries [16, 19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…We presented the first approach at assessing the effectiveness of 3D shape and surface radiomic features extracted from the tumor habitat (enhancing lesion, and T 2w /FLAIR hyperintense peri-lesional regions) to differentiate tumor progression from PsP on conventional MR scans (Gd-c T 1w , T 2w , FLAIR). Our work was based on the rationale that there are observable 3-dimenstional shape and surface irregularities encountered on the enhancing lesion as well as the perilesional boundaries in patients with tumor recurrence (potentially due to aggressive tumor infiltration and disruption) as compared to those with benign pseudoprogression, which will likely have more regular boundaries [16, 19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Application of a threshold based on naïve controls or shape analysis of tumor ROI fluorescence may help to further distinguish tumor from background. 34 We also demonstrated that FUS-assisted delivery of LS301 can significantly enhance tumor contrast at time points in tumor progression when BBB is intact, preventing access of intravenously administered molecular probes to brain tumors. This finding illustrates how a combination of tumor-targeting molecules and transient BBB disruption can additively augment both tumor uptake and retention in the brain.…”
Section: Discussionmentioning
confidence: 73%
“…One can reexpress the data using coordinates of this subspace via the principal coefficients in ℝ r computed as ci=UrTvi,0.5emi=1,,n. One can then use these principal coefficients for further modeling, for example, PC regression (Bharath et al, ).…”
Section: Statistical Summaries Of Shapesmentioning
confidence: 99%
“…(a) Laga et al [2014] (b) Srivastava et al [2009] (c) O'Higgins and Dryden [1992] (d) Bharath et al [2018] (e) Kurtek et al [2012] (g) Kaziska and Srivastava [2006] (f) Joshi and Srivastava [2009] F I G U R E 1 Applications of statistical shape analysis include (a) leaf shape classification, (b) facial recognition, (c) anthropology, (d) tumor shape modeling, (e) clustering of diffusion tensor magnetic resonance imaging fibers, (f) military defense, and (g) gait recognition…”
Section: Applications Of Landmark-and Curve-based Shape Analysismentioning
confidence: 99%
See 1 more Smart Citation